On optical solitons of the resonant Schrodinger's equation in optical fibers with dual-power law nonlinearity and time-dependent coefficients - Kilic, Bulent; İnç, Mustafa (Taylor & Francis Ltd, 2015)
In this paper, the generalized tanh method is used to construct dispersive optical solitons for the resonant Schrodinger's equation with dual-power law nonlinearity and time-dependent coefficients. Some optical solitons of this equation have been obtained. We have proved that the terms of equation, like velocity, are effected by examined dependent coefficients terms of the equation.
Keywords: 1St Integral Method; Wave-Equations; Expansion